Housing estate greenery in shaping the quality of housing environment on the example of Bialystok - Baum, Marta (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The housing environment is the basic area of ​​human functioning, which via its quality affects the state of people’s health and well-being. One of the main factors determining the high quality of the housing environment is an appropriate indicator of green areas per 1 inhabitant, which gives the opportunity to create friendly common spaces as well as the nature of the greenery itself. The article presents the analyzes of selected Białystok housing estates which implementation was based on various guidelines and indicators regulating the size of green areas in housing estates. The conducted research allowed to state that urban norms applied in the 20th century provided the best indicator of green areas per capita. Replacing them with a biologically active area ratio has minimized green areas in housing estates and it is becoming necessary to develop new urban indicators to improve the quality of the housing environment.